2017
DOI: 10.1097/njh.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating End-of-Life Care Education Within Nursing Programs

Abstract: Many nurses report feeling ill prepared through their formal education to competently care for dying patients and their families. These deficits signal a need for curricular reform; however, current practices in the provision of palliative and end-of-life (EOL) care education must first be systematically evaluated to guide these reforms. This article will share the findings of a pilot study in which the context, input, process, and product evaluation model was used to guide a detailed evaluation of palliative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Previous research has noted that inadequate confidence in nurses may influence the quality of palliative care they provide (Lippe et al, 2017). In particular, Pesut et al (2014) have revealed positive effects of palliative care education interventions on nurses' knowledge, abilities, and attitudes regarding care for dying people in several settings.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Previous research has noted that inadequate confidence in nurses may influence the quality of palliative care they provide (Lippe et al, 2017). In particular, Pesut et al (2014) have revealed positive effects of palliative care education interventions on nurses' knowledge, abilities, and attitudes regarding care for dying people in several settings.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The framework is not inhibited by assumptions of logic models [47] and is underpinned by the principles of the Joint Committee on Standards for Educational Evaluation [40]. CIPP has been widely used to evaluate health care services [49][50][51], educational and training programs [47,[52][53][54], and webinars [55]. The CIPP model enables evaluators to design specific core questions for each evaluation type that are relevant to the intended project to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Efforts have been made, therefore, to specify what education nurses should receive, [16][17][18] what competencies to be mastered, 19,20 and what practice to be implemented 21,22 to provide high-quality PEOL care for patients and their families. Several tools were also developed to assess PEOL care education, 23,24 practice, [25][26][27] and perceived competence. [28][29][30] However, a comprehensive, psychometrically robust instrument to assess PEOL care education, practice, and perceived competence among ICU nurses does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…Existing tools are criticized for being too long, 23,24 of poorly reported psychometric properties, 25,31,32 of a limited focus to a particular setting or subpopulation, 26,32,33 of a limited focus on the end of life period, 27,29,34 or not providing precise data on all domains of PEOL care. 30,35 Existing tools often assign different weights to different care domains, 33,36 and therefore, domains are not comparable without scores transformation, which is often not done.…”
Section: Introductionmentioning
confidence: 99%